INDICATORS OF QUALITY OF LIFE FOR PATIENTS WITH POLLEN ALLERGY: A COMPARISON OF DIFFERENT TREATMENT OPTIONS - Asalov Giyosiddin (Scholar Express Journals, 2025)
Allergic diseases are a significant issue in modern medicine. According to the World Health Organization (WHO), allergic diseases rank third among common diseases. Epidemiological data suggests that approximately 10- 30% of the population suffer from allergies, and this number can reach up to 50% in some cases after 20 years. Through a series of studies, it has been estimated that allergic diseases affect 25% of the world's population, with varying incidence rates between countries. Sensitivity to respiratory allergens plays a major role in the development of respiratory allergies
Keywords: pollinose; dermatophagoides; bronchial asthma